Solve for x , where:
2 x − 4 − 2 x = − 1 5 .
Bonus: Try to solve the equation algebraically, not just through guessing and checking.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can't take natural logarithms directly. Note that lo g 2 x − 4 − 2 x is not equal to ( x − 4 ) − x .
Yes, that is the point of the question. I wanted to make it so that you couldn't directly take the logarithm of both sides, forcing people to do some algebraic manipulation.
2 x − 4 = 2 4 2 x so we can rewrite the equation as 2 4 2 x − 2 x = − 1 5
If we then take 2 x = y we can simply solve for y .
2 4 y − y = − 1 5
1 6 y − y = − 1 5
Factorising y we get ( 1 6 1 − 1 ) y = − 1 5
1 6 − 1 5 y = − 1 5
Divide by − 1 5 on both sides
1 6 1 y = 1
Multiply by 16 on both sides
y = 1 6
y = 2 x
⇒ 2 x = 1 6
l o g 2 2 x = l o g 2 1 6
x = 4
2 x − 4 − 2 x = − 1 5
2 x ∗ 2 − 4 − 2 x = − 1 2
2 x ( 2 − 4 − 1 ) = − 1 5
2 x = 1 6
2 x = 2 4
x = 4
Problem Loading...
Note Loading...
Set Loading...
We can see that simply taking the natural logarithm of both sides does not yield a solution, so to solve this, we must first see that:
2 x − 4 = 2 4 2 x = 1 6 2 x
Then:
1 6 2 x − 2 x = − 1 5
We can then multiply both sides by 1 6 :
2 x − 1 6 ( 2 x ) = − 2 4 0
We can then see that we have like terms, with different coefficients, so we can now subtract the two expressions:
− 1 5 ( 2 x ) = − 2 4 0
Then:
2 x = 1 6
We can then take the logarithm of both sides, with base 2 , or we can take the natural logarithm of both sides with the base change and see that:
x = 4